Controllable morphology and self-assembly of one-dimensional luminescent crystals based on alkyl-fluoro-substituted dithienophenazines. Issue 12 (6th March 2018) - Song, Xiaoxian; Yu, Hanbo; Zhang, Yuewei; Miao, Yang; Ye, Kaiqi; Wang, Yue
Abstract : A class of dithienophenazine derivatives, 9, 10-difluoro-2, 5-dialkyldithieno[3, 2- a :2′, 3′- c ]phenazine (F- n, n = 4, 5, 6, 7 and 8), modified with various lengths of linear alkyl chains were synthesized and used as building blocks to assemble luminescent one-dimensional (1D) nano/microcrystals. Abstract : A class of dithienophenazine derivatives, 9, 10-difluoro-2, 5-dialkyldithieno[3, 2- a :2′, 3′- c ]phenazine (F- n, n = 4, 5, 6, 7 and 8), modified with various lengths of linear alkyl chains were synthesized and used as building blocks to assemble luminescent one-dimensional (1D) nano/microcrystals. It was demonstrated that the side-chain length can dramatically influence the self-assembled morphologies of the 1D nano/micromaterials. The self-assembly behaviors of F- n have been studied based on the methods of crystallization in the solution phase and solvent evaporation on a substrate. For F-4, F-6 and F-7 molecules, well-defined 1D twisted microstructures (including ribbons, fibers and bundles) were obtained. F-5 molecules can self-assemble into nearly criss-cross (orthogonal) network patterns interconnected by 1D wires. F-8 molecules with longer alkyl chains predominantly formed flattened wires. Single crystal X-ray structure studies of F- n ( n = 4, 5 and 8) demonstrated that alkyl chains with different lengths result in distinctly different intermolecular interactions and molecular packing modes, which provides a reasonable explanation for the alkyl chain length-dependent assembly morphologies and emission of F- n -based nano/micromaterials. It has been demonstrated that anisotropic noncovalent interactions and mirror-symmetrical crystallization dominated the 1D assembly behaviors of this class of molecules.